Literature Review of Basic Badminton Skills Learning in School Physical Education - Ishak, Muhammad; Nawir, Nukhrawi (Journal of Sport Education, Coaching, and Health (JOCCA), 2025)
This literature review examines current trends, methodologies, and outcomes in teaching basic badminton skills within school physical education (PE) programs. A systematic review process following the PRISMA guidelines identified 187 studies, with 20 peer-reviewed articles meeting the inclusion criteria for final analysis. The review highlights a growing shift from traditional direct instruction toward innovative pedagogical models such as Teaching Games for Understanding (TGfU), Sports Education, and hybrid approaches. For example, a study by Gil-Arias et al. (2018) revealed that TGfU increased students’ decision-making and gameplay performance by 32% compared to control groups. Similarly, Chen et al. (2020) demonstrated that integrating game-based learning improved serve accuracy by 27% among junior high students. Technology-enhanced instruction also emerged as a critical factor, with Lin et al. (2021) reporting that wearable motion sensors contributed to a 23% increase in double coordination among participants. Peer-assisted learning and cooperative strategies were shown to enhance skill acquisition, motivation, and self-efficacy (Huang & Tongdecharoen, 2024). The studies also emphasize the importance of assessment tools tailored to badminton, as noted by Williyanto et al. (2018), who developed a reliable and valid rubric for measuring fundamental skills. Despite these positive outcomes, barriers such as inadequate facilities, large class sizes, and limited teacher training continue to hinder effective implementation. The findings suggest the need for comprehensive teacher development programs and curriculum alignment to support the application of contemporary instructional models.